Evaluasi Kinerja: Apakah Itu Penting? - Ipad Fajrillah; Yuyun Wahyuni; Dewi Kania (Prosiding Amal Insani Foundation, 2023)
Performance evaluation is an important thing that every organization must do. This is to determine the performance, be it in organizations, individuals, or groups. With performance evaluation, the organization will find it easier to determine future performance achievements. Ultimately it will fail to determine its direction and purpose. The method used in this study is to find relevant sources of how performance evaluation should be carried out. Working on performance evaluation is a challenging thing. The organization must know several techniques to evaluate performance. This article also explains the importance, reasons, systems, benefits, processes, methods, and errors in performance evaluations. Thus, this is expected to be a guide in conducting performance evaluations in an organization.